PERAN MEDIASI MOBILE BANKING PADA KUALITAS LAYANAN, NILAI, DAN KEPUASAN NASABAH BSI TANGERANG - Alim, Muhammad Nurul; Maulana, Irwan; Suwarno, Rizky (STAI Asy-Syukriyyah, 2025)
This study examines the mediating role of mobile banking in the relationship between service quality, customer value, and customer satisfaction at Bank Syariah Indonesia (BSI). Utilizing a quantitative approach with a survey method, the research involved 100 BSI customers in Tangerang City, selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS-SEM). The findings reveal that both service quality and customer value have a positive and significant impact on mobile banking usage, which subsequently enhances customer satisfaction. Furthermore, service quality and customer value were found to exert a direct and significant influence on satisfaction levels. The results confirm that mobile banking serves as a partial mediator in these relationships. These findings underscore the necessity of optimizing digital service quality and perceived value to strengthen customer satisfaction within the Islamic banking sector.